Converging on quality: Examining multiple measures of teaching effectiveness. (June 2019) - Sandilos, Lia E.; Sims, Wesley A.; Norwalk, Kate E.; Reddy, Linda A.
Abstract: The present study explores the convergent and predictive validity for several widely used measures of teaching quality from the Measures of Effective Teaching Project (Bill and Melinda Gates Foundation, 2009-2011). Specifically, the Classroom Assessment Scoring System (CLASS; Pianta, Hamre, & Mintz, 2012), the Framework for Teaching (FFT; Danielson Group, 2013), and the Tripod Student Perceptions Scale (Tripod; Ferguson, 2008) were examined. Correlations among measures were assessed by developmental level and content area (elementary mathematics N  = 70; elementary English language arts N  = 101; middle school mathematics N  = 291, middle school English language arts N  = 280). Both average scores and score variability (i.e., coefficient of variation) for the CLASS, FFT, and Tripod were used to predict value-added models (VAM), a high-stakes measure of students' academic growth. For elementary mathematics and ELA, findings indicated the CLASS and FFT exhibited moderate convergent validity while divergent validity was found between the Tripod and the CLASS and FFT. Across content areas in middle school grades, the CLASS, FFT, and Tripod exhibited moderate to high-moderate convergent validity. Average student and observer scores were positively related to VAM scores, whereas variability in scores demonstrated negative relations to VAM scores. Implications of findings for teacher evaluation and professional development are discussed. Highlights: Some divergence between observations and student ratings in elementary grades Greater convergence between observations and student ratings in secondary grades Average student and observer scores positively related to value-added scores Variability in student and observer scores negatively related to value-added scores